Identifying groups of entrepreneurial activities at universities - David Pickernell (International Journal of Entrepreneurial Behavior & Research, 2018)
Purpose – The purpose of this paper is to identify whether the entrepreneurial activities of universities in the UK can be statistically grouped together. Design/methodology/approach – This paper is performing a principal component analysis (PCA) of the 2009/2010 UK Higher Education Business and Community Interaction Survey (HE-BCIS) data for the third stream activities of universities in the UK.Findings – The PCA of the 144 included institutions identified four groups of entrepreneurial activities being engaged in by universities in the UK. Three of the four groups were related to spin-offs, labelled as “Staff Spin-off Activity”, “Non-HEI Owned Spin-Off Activity” and “Graduate Start-up Activity”. The remaining factor has been named “University Knowledge Exploitation Activity (UKEA)” and encompasses a wide range of university knowledge creation, exchange and exploitation activities.Research limitations/implications – The research indicates, through a ranking system for eachuniversity for the various groups of entrepreneurial activities, that universities are often entrepreneurial in just one or two of the groups of entrepreneurial activities identified by the PCA. Identifying what is causing those differences is required to further understand why we see this variation across the HE sector.Originality/value – The use of a PCA to identify groups of entrepreneurial activities is a novel approach. Typically studies use a select few indicators, such as spin-offs or patents to analyse the entrepreneurial activities of universities. This study uses PCA to group together statistically related activities which can then be used to identify what is driving these groups of activities in future studies.